Millennials as an adequate target for disruptive mobile banking apps : Montepio case - Pinheiro, Bernardo Lobo Vilela da Silveira (2018)
Nowadays, society is relentlessly moving towards an increasingly digitalized panorama where the banking industry is expected to continue playing an invaluable role. In the aftermath of a crisis period that brought great turmoil to European markets, banks were submitted to stricter regulation and tighter capital requirements that have deeply influenced their operations. Recently, there have been legislative reforms within the European community that will ultimately open the door to non-traditional financial institutions that wish to operate in the banking sector. This is the case of technological start-ups that are specialized in financial services, such as FinTech companies – currently marketing their innovative mobile banking apps in several countries across a growingly digitalized world. Many traditional retail banks are already accelerating the pace, in a race against Time, reshaping business models to provide the modern consumer with a disruptive banking experience. This Thesis proposes Millennials as an appropriate segment for financial institutions to target, in order to successfully implement their mobile banking applications. By combining the knowledge gathered from academic literature and the results obtained via a thorough assessment on 195 Millennials that have answered an online questionnaire, the researcher endeavours to define if this generation is indeed an adequate target and how should mobile banking apps be designed and marketed, considering the characteristics of this final consumer.